2009
DOI: 10.1016/j.neuron.2008.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Modulation of Limbic Dopamine D3 Receptors by CaMKII

Abstract: Summary Ca2+/calmodulin-dependent protein kinase II (CaMKII) is central to synaptic transmission. Here we show that synaptic CaMKIIα binds to the third intracellular loop of the limbic dopamine D3 receptor (D3R). This binding is Ca2+-sensitive and is sustained by autophosphorylation of CaMKII, providing an unrecognized route for the Ca2+-mediated regulation of D3Rs. The interaction of CaMKIIα with D3Rs transforms D3Rs into a biochemical substrate of the kinase and promotes the kinase to phosphorylate D3Rs at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(133 citation statements)
references
References 56 publications
3
130
0
Order By: Relevance
“…Recent work showed that the activation of CaMKII has a key role in the development and maintenance of the addiction state, and that fast and slow positive feedback loops are interlinked through CaMKII underlying drug addiction (Li et al, 2008). Recent work by Wang and colleagues showed that CaMKIIa could relieve the D3R-mediated inhibition on sensitized behavior to foster drug-seeking behavior, implicating CaMKIIa as an important negative regulator of D3R (Liu et al, 2009). In our experiments, we analyzed the effects of different isoforms of CaMKII on drug reinforcement responses.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work showed that the activation of CaMKII has a key role in the development and maintenance of the addiction state, and that fast and slow positive feedback loops are interlinked through CaMKII underlying drug addiction (Li et al, 2008). Recent work by Wang and colleagues showed that CaMKIIa could relieve the D3R-mediated inhibition on sensitized behavior to foster drug-seeking behavior, implicating CaMKIIa as an important negative regulator of D3R (Liu et al, 2009). In our experiments, we analyzed the effects of different isoforms of CaMKII on drug reinforcement responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported recently that CaMKII phosphorylation causes desensitization of D 3 receptors (Liu et al, 2009) and also D 2 receptors (JQ Wang, personal communication), both (Beckstead et al, 2004;Davila et al, 2003). Furthermore, activation of D 2 receptors, as well as D 4 receptors, has been shown to activate CaMKII via G i/o and intracellular Ca 2 + release (Gu and Yan, 2004;Takeuchi et al, 2002).…”
Section: Ca 2 + -Dependent Desensitization Of D 2 Receptor-mediated Imentioning
confidence: 95%
“…CaMKII interacts with many types of Ca 2þ channels and transmitter receptors including L-type voltage-sensitive calcium channels (VSCCs) (Hudmon et al 2005;Wheeler et al 2008), T-type VSCCs (Welsby et al 2003), P/Q-type VSCCs (Jiang et al 2008), dopamine receptors (Liu et al 2009), muscarinic receptors (Guo et al 2010), and the NR2B subunit of NMDAR (Bayer et al 2001;Merrill et al 2005). This naturally leads to the hypothesis that opening of specific channels activates bound pools of CaM-KII via nanodomain Ca 2þ .…”
Section: Camkiimentioning
confidence: 99%